PERAN TRANSFORMASI DIGITAL DALAM MEMEDIASI KEPEMIMPINAN DIGITAL DAN KOMPETENSI TEKNOLOGI TERHADAP KINERJA PEGAWAI DI BADAN PUSAT STATISTIK KOTA MANADO - Sylvia Tambeo; Hendra Tawas; Merinda H. Ch. Pandowo (Magister Manajemen Program Pasca Sarjana Universitas Sam Ratulangi Manado, 2026)
This study aims to examine the role of digital transformation in mediating the relationship between digital leadership and technological competence and employee performance at the Centra Statistics Agency (BPS) in Manado. This study uses a quantitative research design, with 33 employees of the Manado City Statistics Agency (BPS) serving as the research subjects. The data collection process used a saturated sampling technique, which means that every member of the population, without exception, was included in the research sample; data were collected by distributing questionnaires. The data were analyzed using Structural Equation Modeling (SEM) with SmartPLS 3.0. The results of this study indicate that Digital Leadership does not have a direct effect on Employee Performance. However, trough the mediation of Digital Transformation, Digital Leadership has a significant effect on Employee Performance. Meanwhile, technological competence whether directly through the mediation of digital transformation has a significant impact on employee performance. The results indicate that digital transformation has been shown to play a crucial role in optimizing technological competence to drive improvements in employee performance. Similarly, digital transformation has also been shown to play a crucial role in optimizing digital leadership to drive improvements ini employee performance.